Pengaruh Kegiatan Reading Time Terhadap Kemampuan Literasi Informasi Siswa di Perpustakaan SMA N 1 Jetis - Ajeng Diah Mawartiningsih; Dr. Sri Rohyanti Zulaikha, S.Ag., SS., M.Si. (UIN Mataram, 2021)
This study aims to determine the impact of Reading Time activities on students' information literacy skills in the library of SMA N 1 Jetis. The research method used in this research is descriptive quantitative. The sample obtained amounted to 74 respondents with the Yammane formula. The sampling technique used incidental sampling. Variable X is Reading Time activity as independent variable, Y variable is information literacy ability as dependent variable. Data collection techniques are questionnaires, interviews, observation, and documentation. The measurement scale uses a Likert scale. Data analysis used the mean and grand mean, correlation analysis and simple linear regression analysis. The results showed: (1) Reading Time Activities in the Library of SMA N 1 Jetis were included in the